Les interactions entre la politique de la Réserve fédérale et l’innovation, une clé de lecture de la « nouvelle économie » aux États-Unis - Ruxandra Pavelchievici (Revue LISA)
This article is an analysis of the interactions between monetary policy and innovation in the United States during the 1990s, known as the “new economy” era, and rests on the hypothesis that they resulted in an unprecedented macroeconomic configuration. Its object is to show how the Federal Reserve made its policy credible and transparent, and thereby contributed to creating a climate that was favourable to innovation. Innovation is then analysed in the light of its implications for monetary policy by considering the stance adopted, as well as the Federal Reserve’s perception of stock market speculation.